Pore Water Pressure Assessment in the Impervious Core of the Karkheh Dam During Simultaneous Construction and Impounding - S.M M.HOSEINI; M M; R A (مهندسی منابع آب, 2009)
The Karkheh River , which originates in the Zagros Mountain Ranges, is the third largest river in western I.R. Iran, flows through the Khusistan Plain and drains into the Persian Gulf . The Karkeh Earth Dam, which is 3030 m long and 128 m high with an initial capacity of 7 billion m3, was constructed during the 1992-2001 period. The conglomerate and mudstone strata outcrops at the dam site provide the needed strength and water tightness for the foundation and abutments. The stability analyses under both static and dynamic conditions have been performed employing appropriate software programs, and slope displacement of the up-and downstream shells has been verified. The great value of water in dry lands dictates that impoundage should start as soon as the construction stages permit. The development of pore water pressure (PWP) in the clay core due to the seepage of the impounding water, which is supplemented by the loading of the fill material, enhances the probability of hydraulic fracturing of the core. PWP development in the core during impoundage was simulated using the CA2 Software. The output data were agreeably similar to the instrument readings. We conclude that both the PWP and fill loading significantly impact the stability of the Karkheh Earth Dam core